Oscar Wilde and classical antiquity - Blanshard, Alastair; Blanshard, Alastair; Manny, Iarla; Manny, Iarla; Riley, Kathleen; Riley, Kathleen (Oxford University Press, 2017)
Celebrated now and during his lifetime as a wit and aesthete, Oscar Wilde was also a talented classicist whose writings evince an enduring fascination with Graeco-Roman antiquity. This volume explores the impact of the classical world on his life and work, offering new perspectives on canonical texts and close analyses of unpublished material